2022
DOI: 10.1038/s43247-022-00604-5
|View full text |Cite
|
Sign up to set email alerts
|

Humidification of Central Asia and equatorward shifts of westerly winds since the late Pliocene

Abstract: The production, transport, and deposition of mineral dust exert major influences on climate change and Earth’s biogeochemical cycles. Furthermore, their imprint, as recorded in pelagic sediments, provides an avenue for determining past changes in terrestrial aridity and atmospheric circulation patterns in response to global climate change. Here, by examining geochemical and magnetic data obtained from a ferromanganese crust in the western Pacific Ocean, we investigate the eolian dust source-region conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…These data imply different sources and geochemical behavior of Fe in the WP research area. According to previous source‐tracing studies on geological records from the North Pacific regions (e.g., Rea et al., 1998; Uno et al., 2009; Zhong et al., 2022), the reversed correlations between Fe, Mn, and REY shown by the WP sediment cores might be related to the Asian dust input. Our XRD mineral characterizations reveal the occurrences of detrital minerals (e.g., quartz and muscovite) in the studied WP and CNP cores, but only the WP core shows a different trend of Fe versus REY.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These data imply different sources and geochemical behavior of Fe in the WP research area. According to previous source‐tracing studies on geological records from the North Pacific regions (e.g., Rea et al., 1998; Uno et al., 2009; Zhong et al., 2022), the reversed correlations between Fe, Mn, and REY shown by the WP sediment cores might be related to the Asian dust input. Our XRD mineral characterizations reveal the occurrences of detrital minerals (e.g., quartz and muscovite) in the studied WP and CNP cores, but only the WP core shows a different trend of Fe versus REY.…”
Section: Discussionmentioning
confidence: 82%
“…The influence of eolian input on the WP research area is variable and influenced by the speciation of Fe, which is controlled by the environmental conditions of the source regions (Zan et al., 2023; Zhang et al., 2020). In addition, sediment cores (e.g., Pettke et al., 2002) and submarine Fe‐Mn deposits (e.g., ferromanganese crust, Zhong et al., 2022) revealed that the northward/southward shifts of the westerly winds may also influence the dust flux and sources. For example, desert dust originating from long‐term weathering contains more highly oxidized Fe(III), which remains stable and can precipitate into the ocean bottom (Schroth et al., 2009; Shoenfelt et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Using geochemical and magnetic data obtained from a ferromanganese crust in the western Pacific, together with climate models, Zhong et al . (2022) interpret their data to suggest an equatorward shift of the westerly jet and humidification of Central Asia during the gradual transition from a warm Pliocene climate to the cool Pleistocene, between ∼2.5 and 2.7 Ma. This time interval coincides with our inferred increase in C 4 coverage (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The second period of C 4 expansion beginning at ~3.5 Ma and punctuated by a rapid increase at ~2.5 Ma is inferred to be of greater magnitude and does not appear in records from either terrestrial palaeosols or marine sediments from the Bengal Fan, though the temporal resolution of these records is typically of insufficient resolution during this time interval. Using geochemical and magnetic data obtained from a ferromanganese crust in the western Pacific, together with climate models, Zhong et al (2022) interpret their data to suggest an equatorward shift of the westerly jet and humidification of Central Asia during the gradual transition from a warm Pliocene climate to the cool Pleistocene, between ~2.5 and 2.7 Ma. This time interval coincides with our inferred increase in C 4 coverage (Fig.…”
Section: C Climatic Implications Of Inferred C 3 -C 4 Transitionmentioning
confidence: 99%
“…Following the gradual growth of the NH ice sheet, the Hadley Circulation has grown stronger since the Pliocene (Brierley et al., 2009; Etourneau et al., 2010; Fedorov et al., 2015; Jia et al., 2008) while associated westerlies have intensified and moved equatorward (Abell et al., 2021; Taylor et al., 2022; Zhong et al., 2022). Yet for the ITCZ, large uncertainties lie not only in the influence of the NH ice sheet but also in the influence of the western Pacific warm pool (WPWP) which modulates three‐dimensional seawater temperature gradients in the Pacific.…”
Section: Introductionmentioning
confidence: 99%